2014
DOI: 10.1038/jhh.2014.113
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D receptor gene polymorphisms and plasma renin activity in essential hypertensive individuals

Abstract: Several studies analyzed 25-hydroxyvitamin D (25[OH]D) and blood pressure (BP) relationship with mixed results. Moreover, a relationship between the risk of hypertension and vitamin D receptor (VDR) gene polymorphisms, FokI and BsmI, was reported. This study was aimed to analyze these relationships in essential hypertensive (EH) patients. Seventy-one EH patients, 18-75 years old, were enrolled. Patients underwent clinical BP, 24-h ambulatory BP monitoring, 25[OH]D and plasma renin activity (PRA) evaluations. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
(47 reference statements)
0
9
0
Order By: Relevance
“…Both studies attributed elevated blood pressure or hypertension to enhanced production of renin and angiotensin II due to the effect of FF homozygotes. Cottone et al (33) explored hypertensive Italian participants and did not detect a significant link between the FokI VDR polymorphism and blood pressure or between blood pressure and serum 25(OH)D levels. Future research may demonstrate a strong link between FokI VDR polymorphisms and maternal hypertension.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both studies attributed elevated blood pressure or hypertension to enhanced production of renin and angiotensin II due to the effect of FF homozygotes. Cottone et al (33) explored hypertensive Italian participants and did not detect a significant link between the FokI VDR polymorphism and blood pressure or between blood pressure and serum 25(OH)D levels. Future research may demonstrate a strong link between FokI VDR polymorphisms and maternal hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have uncovered a link between the VDR gene polymorphism and dyslipidemia, supporting this relationship (18,19,33,34). Schuch et al (2) found, for example, that participants who did not suffer from MetS and carried the mutant homozygous genotype (ff) exhibited significantly higher TG levels and lower HDL levels when compared to study participants who possessed the heterozygous (Ff) or normal homozygous (FF) genotypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cottone and coauthors [29] conducted a study in 71 patients with essential hypertension and 72 control subjects, of both sexes, aged 18-75 years, in Italy. The frequencies of FF, Ff, and ff genotypes in hypertensive patients were 50.7%, 42.3%, and 7.0%, respectively, and in control subjects were 40.3%, 50.0%, and 9.7%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…A study on an Indian cohort also found important associations between hypertension and Fok I VDR polymorphism [rs2228570], which generates long and short variants of the VDR, independent of sex, family history and smoking [126,127]. However, allelic frequencies and genotype distribution of FokI and BsmI VDR polymorphisms were not found associated with hypertensive status or renin activity in a small study on Italian individuals with essential hypertension [128]. A recent meta-analysis reported that polymorphism in the 24-hydroxylase (CYP24A1) gene, which controls vitamin D metabolism, were the most significantly associated with systolic and diastolic blood pressure [129].…”
Section: Vitamin D and Arterial Hypertensionmentioning
confidence: 98%